From Chaplaincy to Spiritual Care: Turning points for an emerging health profession - Cheryl Holmes (ACHSM, 2021)
Objectives: National standards in Australia acknowledge the significance of spiritual care in the provision of holistic care, understanding that peoples' beliefs and values impact their experience and health outcomes. While spiritual care has been provided in Australian hospitals for many decades little attention has been given to changes in the workforce and the implications for quality of care. This study aimed to further understanding of the key influences and mechanisms for change to ensure safe and high-quality spiritual care provision in Australia by a qualified and credentialed workforce. Methods: This study used a qualitative case study design which included interviews and analysis of archived records. Narrative analysis produced an extensive organisational case study from which a timeline of key changes significant to the spiritual care workforce was constructed to inform this paper.  Results: There have been movements towards a professional spiritual care workforce, but progress has been slow, and inconsistency persists across Australia. Five key influences were identified that provide a basis for future progress: the need for evidence, cooperation amongst stakeholders, investment by government and health service management, and leadership and advocacy from spiritual care peak bodies. Conclusions: Attention to historical turning points enables understanding of the influences for change. These can become opportunities for health management to further progress towards a qualified and credentialed spiritual care workforce able to deliver safe and high-quality spiritual care.